Analysis of Cash Ratio, Firm Size and Return on Assets that Influence Dividend Payout Ration Soe Companies Listed on the Indonesia Stock Exchange - Ester Sitepu (International Journal of Applied Finance and Business Studies, 2022)
This study aims to determine whether the Influence cash ratio, firm size and return on assets influence simultaneously and partially to the dividend payout ratio At the state-owned company Listed on the Indonesia Stock Exchange. The method of this thesis is a descriptive statistical analysis, the classic assumption test, and hypothesis testing. Independent variables in this study is the cash ratio, firm size and return on assets while Dependent variable is the dividend payout ratio with a sample size of this study as many as 54 by using purposive sampling acquired 18 companies over three years. The type of data used is secondary data. The results of this study demonstrate that, in sumultaneous cash ratio, firm size and return on assets has no effect simultaneous dividend payout ratio in the state-owned company. In partial cash ratio, and return on assets have no effect and firm size affect the dividend payout ratio.